(untitled) (Al-Aasar, 2025)
Here Khalil Ali Khan Ashak has portrayed the superstition existing in the society.He throws light on how the people act upon considring it final whatever is said by the Hakeems. It is impossible to turn down whatever is ordered by a Pir or Hakeem.Here he elaraborates this fact by a story of a king named Kabo Kamran ,his forty ministers and a Hakeem ,descendent of prophet Daniyal who became a victim of superstition of a Hakeem and lost their lives.